AN EXPERIMENTAL STUDY OF KRYPTON DIFFUSION AND SOLUBILITY IN SILICIC GLASSES - Carroll M.R.; Sutton S.R.; Rivers M.L.; Woolum D.S. (My University, 1993)
Kr diffusivity and solubility have been measured in glasses of SiO2, NaAlSi3O8, KAlSi3O8 and rhyolitic composition, under experimental conditions ranging from 700° to 950°C and 215 to 3150 bar. Kr diffusion in SiO2 (Sil) and NaAlSi3O8 (Alb) glass compositions at 700–950°C can be described by the following Arrhenius relations, with D in cm2 s−1, E in cal mol−1, T in kelvins: Limited data for rhyolite suggest Kr diffusivities similar to those measured in Alb, while one experiment on orthoclasic glass (800°C) shows Kr diffusivity to be ∼ 16 times faster than in Alb at the same temperature. The data on Kr diffusivity agree with trends of increasing activation energy and decreasing diffusion rates as the gas atom size increases, as observed for He, Ne and Ar in amorphous silicates. The measured Kr solubilities in Alb and Sil are independent of temperature and are an approximately linear function of pressure up to at least 415 bar and possibly to several kilobars although we have only a small number of higher-pressure experiments. The new results for Kr and published data on He, Ne and Ar solubility clearly document large solubility variations which depend both on silicate composition and gas atom size, with highest solubilities observed for the smallest gas atoms in the most silica-rich melts/glasses. There is a good correlation between Kr solubility and melt ionic porosity in ultramafic through rhyolitic melt compositions; this provides a useful tool for predicting Kr solubilities in melt compositions that have not been studied experimentally. In natural systems the changes in noble gas solubility due to melt composition differences will far exceed changes due to temperature effects on solubility.